Norske drapsmenn (og kvinner) 1955-1982 - Hilde Dahl (Nordisk Tidsskrift for Kriminalvidenskab)
Abstract: Homicides are rare in Norway; the country’s homicide rate is among the lowest in the world (UNODC, 2013). This might be why homicides always receive attention in the national news. The topic has also received attention on a governmental level. Reducing the number of homicides is an expressed goal in several official reports. However, preventive efforts require knowledge. While a handful of studies have been conducted using a variety of disciplinary approaches and methods, several recent reports point out that homicide is not a prioritized research field in Norway (NOU 2010:3; FHI rapport, 2012; JBD, 2018). This is the first article from the project »Homicides in Norway, 1955-1982, a historical-criminological study«. Studies using historical methods on homicide in the contemporary era have not previously been conducted in Norway. The projects aim is to provide historical insight into the rates and patterns of Norwegian homicide during the period 1955 to 1982, based on material originally collected by psychologist Ragnar Christensen (1922-2011) over the course of three decades.